Kedudukan Pemegang Polis dan Pekerja Dalam Hal Terjadinya Kepailitan Pada Perusahaan Asuransi - Kristiani Pasaribu, Mindo; Raffles, Raffles; Manik, Herlina (Universitas Jambi, Fakultas Hukum, 2024)
The aims of this study are 1) to find out and analyze the legal position of policy holders and workers according to laws and regulations in Indonesia, 2) to find out and analyze the regulations regarding protection for policy holders and workers who have provided legal protection or vice versa. This research uses normative juridical research methods with statutory and conceptual approaches. Based on the research results obtained, it can be seen that the position of policy and workers holders in insurance companies that are declared bankrupt through decisions determined by the commercial court is as preferred creditors. In this case, there is a conflict regarding the fulfillment of the rights of policy holders and workers, so to resolve the problem of conflict, legal principles are needed. In this case, the principle of lex posterior derogat legi priori is used, namely that new laws and regulations override old laws and regulations. The Insurance Law is a longer statutory regulation than the Job Creation Replacement Law, so the position of workers in insurance companies that are declared bankrupt has a higher position than the position of policy holders. In terms of the order of fulfillment of rights between the policy holder and the worker, the worker must be paid first. The forms of legal protection for policy holders are regulated in the Civil Code, POJK Insurance and Marketing of Insurance Products, OJK Law, Consumer Protection Law, Bankruptcy and PKPU Law, and Insurance Law. Legal protection for workers is regulated in the Civil Code, Bankruptcy and PKPU Law, PP on Wages, Job Creation Replacement Law, and Constitutional Court Decision Number 67/PUU-XI/2013.